Pulmonary Hyalinizing Granuloma: A Rare Cause of a Benign Lung Mass - Mandeep Singh Rahi; Kulothungan Gunasekaran; Kwesi Amoah; Farheen Chowdhury; Jeff Kwon (Clinics and Practice, 2021)
Pulmonary hyalinizing granuloma (PHG) is a rare, benign lung disease of unknown etiology. It usually manifests as solitary and sometimes as multiple pulmonary nodules. It may have irregular margins, cavitation, or calcifications mimicking metastasis or primary lung neoplasm. It should be considered in the differential diagnosis of pulmonary nodules or masses. In this report, we present an unusual case of incidental slow-growing lung mass in a patient with 30 pack-year smoking history, construction-based occupation. The pleural-based calcified nodule in the left upper lobe gradually increased in size over ten years without any hilar or mediastinal lymphadenopathy. For an accurate diagnosis, PET-scan and histopathological analysis through wedge resection by video-assisted thoracoscopic surgery (VATS) were done. The biopsy findings were consistent with pulmonary hyalinizing granuloma, a rare benign cause of lung mass with an excellent long-term prognosis.